Analisis Perbandingan Biaya Metode Ferosemen dan Bata Ringan Tipe Autoclaved Aerated Concrete (AAC) pada Konstruksi Rumah Tipe 50 di Kabupaten Kediri - M. M. Asrin; Bana Ervadius; Nazilatus Sa'idah (Jurnal Kridatama Sains dan Teknologi, 2026)
The rising costs of construction materials and labor have significantly increased the overall cost of residential construction, making it necessary to identify more economical alternative construction methods without compromising building quality. This study aims to analyze and compare the construction costs of wall work using the ferrocement method and the conventional method employing Autoclaved Aerated Concrete (AAC) blocks in the construction of a Type 50 house in Kediri Regency. The research employed a comparative quantitative approach using the Indonesian National Standard (SNI 2024) Work Unit Price Analysis (AHSP). The data consisted of Type 50 house design drawings, work volumes, material and labor coefficients, and the prevailing prices of construction materials and labor in Kediri Regency. The analysis focused on wall construction by preparing the Bill of Quantities (BOQ) and Cost Estimate (RAB), followed by a comparison of material costs, labor costs, total construction costs, and the efficiency of each construction method.The results indicate that the ferrocement method requires approximately 1.37 m³ of mortar, with cement, sand, and wire mesh as the primary materials, whereas the AAC method uses lightweight concrete blocks, thin-bed mortar adhesive, and plastering. Based on the cost estimation analysis, the total cost of wall construction using the ferrocement method is lower than that of the AAC method, resulting in significant cost savings. In addition to its economic advantage, the ferrocement method offers a lighter structural weight and more efficient use of construction materials. Therefore, ferrocement can be recommended as an economical and technically feasible alternative for wall construction in Type 50 residential buildings in Kediri Regency